A Guideline to Build the Balanced Scorecard Framework : A Case Study at Universiti Utara Malaysia Computer Centre (UUMCC) - Umi Syuhairah, Omar (2004)
Many organizations nowadays more focus and alert on the performance of their organization in order to compete or to become a successful, organized, efficient and effective organization. Balanced Scorecard is one of the techniques of measuring performance. Besides BSC, there are also a lot of performance measurement tools available such as Total Quality Management (TQM), Activity Based Costing (ABC), Balanced Scorecard (BSC), Goal-Question-Metric (GCM) and others. Hence, this thesis aims to propose a guideline to build Balanced Scorecard (BSC) framework for Universiti Utara Malaysia Computing Centre (UUMCC). BSC framework has been developed for the future use of Universiti Utara Malaysia Computer Centre (UUMCC). This thesis used a spiral model as methodology to plan, gathered information and implementation. The BSC framework includes the strategic objective, strategic measurement, target and also initiative for UUMCC. A strategy map for UUMCC is also included in this report. Recommendations, future research, and conclusion will be discussed at the end of this study.